Context-aware techniques for real-time decision making in autonomous mobile robots (Situation awareness Part B) - Sing, Choon Seng (Nanyang Technological University, 2024)
This report examines how simulation-to-real-time errors affect robotic systems, emphasising on sensor mismatches and their implications for obstacle detection. As digital technology and simulation have significantly advanced, robots have a pivotal role to the transformation of industries and human-technology interactions. However, there are potential challenges to apply simulation results to real-world scenarios, especially when it comes to sensor accuracy and calibration. This report addresses issues such as sensor ageing, calibration errors, and data alignment, and explains the complications that arise when robots detect obstacles in a simulated environment versus real-world conditions It is critical to comprehend and tackle these challenges to ensure the reliability and effectiveness of robotic systems in practical applications.